“It’s the same but it’s different”. Gender and violence in same-sex intimacy - Correia de Barros, Isa (2019)
Portuguese gender studies about intimate partner violence (IPV) have been largely focused in opposite-sex relationships. By interviewing five participants (one male and four female), self-identified as victims, we explored how gender may affect same-sex IPV. Four major areas of interest were found: gender performativity; decision to leave the relationship; help-seeking; and language utilized by the participants. It was concluded that more than affecting violence per se, gender may influence victims’ and third parties’ perceptions about same-sex IPV.